Flow pattern of particle contamination in fluid flow through mitre bend - Ainaa Maya Munira Ismail, 1985-; Jamaluddin Md. Sheriff, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012